Tunable electronic and magnetic properties of two‐dimensional materials and their one‐dimensional derivatives. (15th March 2016) - Zhang, Zhuhua; Liu, Xiaofei; Yu, Jin; Hang, Yang; Li, Yao; Guo, Yufeng; Xu, Ying; Sun, Xu; Zhou, Jianxin; Guo, Wanlin
Abstract : Abstract : Low‐dimensional materials exhibit many exceptional properties and functionalities which can be efficiently tuned by externally applied force or fields. Here we review the current status of research on tuning the electronic and magnetic properties of low‐dimensional carbon, boron nitride, metal‐dichalcogenides, phosphorene nanomaterials by applied engineering strain, external electric field and interaction with substrates, etc, with particular focus on the progress of computational methods and studies. We highlight the similarities and differences of the property modulation among one‐ and two‐dimensional nanomaterials. Recent breakthroughs in experimental demonstration of the tunable functionalities in typical nanostructures are also presented. Finally, prospective and challenges for applying the tunable properties into functional devices are discussed. WIREs Comput Mol Sci 2016, 6:324–350. doi: 10.1002/wcms.1251 This article is categorized under: Structure and Mechanism > Computational Materials Science